How a city lost its waterfront : tracing the effects of policies on the sustainability of the Kuala Lumpur waterfront as a public place - Shamsuddin, Shuhana; Abdul Latip, Nurul Syala; Ujang, Norsidah; Sulaiman, Ahmad Bashri; Alias, Nursyahida Alfath (Taylor & Francis, 2013)
Kuala Lumpur owes its beginnings to the two rivers that transect its historic core but it lost its waterfront as a public place due to rapid urbanisation. The rivers were used as flood mitigation measures with limited visual and physical access to the public. This paper traces the effects of policies on the waterfront development of the city by focusing on the factors that contributed to its disappearance. It employs a qualitative approach by analysing the riverfront physical conditions based on old maps and photographs as well as government documents and in-depth interviews with local authority officials, architects and developers.